Seeding of Au on CdSe/CdS nanoplates using Langmuir-Blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2016)
Oleyl amine capped CdSe/CdS nanoplates were synthesized by hot injection technique which formed a stable monolayer over both a water subphase and an aqueous HAuCl4 subphase using a Langmuir-Blodgett trough. Au islands were generated at the edge as well as on one specific surface of the flat nanoplates by exploiting the reducing capacity of oleyl amine to form Au nanoseeds from AuCl4- ions. The initial Au nanoseeds changed to a shell surrounding these nanoplates on prolonged exposure to the subphase containing the Au precursor. Monolayer of the hybrid structures was deposited onto suitable substrates for characterization by a number of different techniques and to study the photocatalytic activity. The same substrate with the monolayers could be re-used in several cycles of photocatalysis.